China’s international education policy amid the post-COVID landscape - Yan, Huang; Jiaqi, Wu (Journal of the Belarusian State University. Sociology, 2023)
To effectively overcome the challenges posed by the COVID-19 pandemic, China have made adjustments to national development plans in various fields such as economics, politics, society, culture, and particularly in education. These adjustments have impacted not only the development direction of the international community but also the national priority development strategy in the post-pandemic era. This paper focuses on China’s higher education and examines the international cooperation it engaged in during the pandemic as well as the relevant policies that were adopted. The analysis shows that these policies have contributed to the acceleration of China’s international education development, furthering its modernisation, localisation processes and paving the way for the development of international higher education in the post-pandemic era in the global context.
Keywords: international higher education; COVID-19 pandemic; Chinese modernisation; localisation of higher education; Sino-Belarusian cooperation